Individual factors that influence the development of spiritual and moral principles in young athletes of military age - Buksha L.F.; Serykh A.B.; Osipova E.V.; Nazarskaya E.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the individual factors that contribute to the development of spiritual and moral principles in young men of military age who participate in sports. Methods and structure of the research. The empirical study was carried out in four regions of the Russian Federation: Arkhangelsk, Kaliningrad, Murmansk and Leningrad regions. The total number of respondents – 1050 respondents – boys in the age range from 16 to 20 years (conscription age). The diagnostics were carried out using the following methods: «Spiritual personality»; «Diagnostics of moral education»; study of the axiological orientation of the individual; study of moral identity. Research results and conclusions. The findings of the study allowed for the identification of individual factors that contribute to the development of spiritual and moral values among young athletes. The study assessed the level of spiritual values, moral upbringing, and axiological orientation (humanistic and pragmatic) of young men of military age, both those who participate in sports and those who do not. The findings are valuable as they can help to enhance the educational and developmental potential of sports activities, which can effectively contribute to the formation of spiritual and moral values among young people in the educational process of secondary and higher educational institutions.